Model of adoption of virtual tools by university students in the context of an emerging economy - López-Sánchez, Jerri Alejandro; Patiño-Vanegas, Juan Camilo; Valencia-Arias, Alejandro; Rojas Coronel, Angel Marcelo (Frontiers in Education, 2024)
Introduction The impact of COVID-19 on higher education has necessitated a reevaluation of teaching methodologies, student engagement, and the integration of information and communication technologies (ICT) as pedagogical tools. This shift creates opportunities for innovation and collaborative learning environments among students. Methods This study aims to investigate the adoption of virtual tools by university students in Medellín. A sample of 373 students was surveyed using a quantitative approach with a descriptive scope. Factor analysis techniques were employed utilizing SPSS software to assess the associative relationships among variables and hypotheses within the framework of the Technology Acceptance Model (TAM). Results The analysis revealed significant correlations, particularly between perceived ease of use and perceived usefulness. Notably, technological devices such as laptops and smartphones were identified as valuable tools for educational purposes, contributing to a positive attitude towards their utilization among students. Discussion The findings underscore the importance of students’ perceptions in shaping their attitudes towards ICT tools for teaching and learning. Understanding these perceptions is crucial for designing effective pedagogical strategies, particularly in crisis situations such as the COVID-19 pandemic, where virtual tools play a vital role in maintaining educational continuity. This study contributes to the ongoing discourse on the integration of virtual tools in higher education, highlighting avenues for further research and practical implications for educators and policymakers.